Didaktika fizike 2 s praktikumom: Zbirka laboratorijskih vaj - Repnik, Robert; Slavinec, Mitja; Klemenčič, Eva (University of Maribor Press, 2022)
Didactics of Physics 2 with Practicum: Collection of Laboratory Exercises. Didactics of Physics with practicum 2 - a collection of laboratory exercises is intended for students of the 3rd and 4th year of the study program Subject Teacher, Orientation Educational Physics at the Faculty of Natural Sciences and Mathematics University of Maribor. Experiments are carried out in the subject Didactics of Physics 2 with a practicum and are divided into seven chapters: Accelerated Motion, Fluid Mechanics, Thermodynamics, Sound, Light, Electromagnetism, and Modern Physics. As part of laboratory exercises, students acquire knowledge and develop skills for the proper performance of experiments in the classroom at the secondary level of education.